A verhulst model for microalgae growth and nutrient removal in domestic wastewater - Jamaian, S. S.; Yusoff2, N. M. (Penerbit UTHM, 2018)
This research aims to investigate the ability of theVerhulst model to estimate the growth of microalgae and the nutrient removal by microalgae in wastewater. First, the Verhulst model is applied to reproduce the previous results of the microalgae Chlorella Vulgaris growth and nutrient removal in different wastewaters. In this research, the result showed a similar agreement. Next, the Verhulst model is implemented to predict the growth of microalgae Botryococcus sp. and nutrient removal by microalgae Botryococcus sp. in domestic wastewater.The growth of microalgae and the nutrient removal by microalgae Botryococcus sp. in domestic wastewater are investigated by using Mathematica software. As a result, the estimation of the microalgae Botryococcus sp. growth and nutrient removal in wastewater can be obtained and thus the microalgae Botryococcus sp.are suitable for treating domestic wastewater.